Building a model of health technology assessment cooperation: lessons learned from EUnetHTA joint action 3. (28th January 2022) - Garrett, Zoe; Imaz-Iglesia, Iñaki; Willemsen, Anne
Abstract: Objective: The European Network for Health Technology Assessment (EUnetHTA) was established in 2006. During its final project phase (joint action 3 [JA3]), it undertook an activity to define the scientific and technical principles of a model of health technology assessment (HTA) cooperation in Europe. This policy article presents the key learnings from JA3 partners about developing a model of HTA cooperation. Methods: There were two phases to the activity: (i) A descriptive phase to describe the elements of HTA cooperation that were already in place in EUnetHTA JA3 and to identify which elements could be improved or were missing. (ii) An analytic phase synthesizing the data collected to identify learnings from the JA3 and to define the scientific and technical principles for a future model of HTA cooperation. Results: Learnings for developing HTA cooperation were identified in regard to the framework used to support the cooperation, the HTA activities undertaken, the involvement of internal and external actors, managing decision making and the required human resources and support services needed to undertake HTA activities and to coordinate collaboration. Conclusions: These learnings coming from the experiences of the EUnetHTA JA3 are useful to inform discussions on a European Union regulation for HTA cooperation as well as subsequent work to set up the structures that will be defined in the regulation. The findings also have broader applicability and are relevant to individuals, groups, and organizations setting up HTA programs or establishing their own international collaborations.